Ant-eating spiders (Araneae: Zodariidae) of Portugal: additions to the current knowledge - Pekár, Stano; Cardoso, Pedro (Zootaxa, 2005)
Three new species of zodariid spiders are described in this paper: Amphiledorus ungoliantae sp. n. and Zodarion bosmansi sp. n. from southern Portugal, and Zodarion atlanticum sp. n. from central Portugal and the Azores. Additional records on another eight taxa from central and southern Portugal are given: Amphiledorus adonis, Zodarion alacre, Z. jozefienae, Z. lusitanicum, Z. maculatum, Z. merlijni, Z. styliferum, and Z. styliferum forma extraneum. To date, there are 19 species (plus one form) of zodariid spiders known from Portugal.